2013
DOI: 10.1002/ctpp.201310016
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of HF‐Plasma Oscilations by means of a Laser‐Heated Emissive Probe

Abstract: Indirectly heated emissive probes have advantages compared to conventional emissive wire probes. We have developed a laser-heated emissive probe consisting of a 1 mm diameter and 2 mm long pin of LaB6, heated by a focussed laser beam of 808 nm wavelength with a power up to 50 W. This probe is smaller and simpler than electrically heated emissive wire probes. Materials of low work function, high temperature stability and longer lifetime such as LaB6 can be used. There is no deformation in a magnetic field and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In a realistic experiment the procedure to verify that the emission current is sufficient for shifting V fl,em as close as possible to Φ pl is to measure V fl,em as function of the EEP heating power P heat . It is very helpful that for increasing heating power the transition from the cold floating potential V fl towards Φ pl (being more positive than V fl by a few time T e -equation (1)) is usually rather abrupt and that above a certain value of P heat the value of V fl,em almost saturates (see for instance [10,30,35,36]). Also figure 1 illustrates the rather abrupt transition of the floating potential of an unheated, or only slightly heated EEP from that of a CLP (horizontal blue line) to that of an EEP, being close to the plasma potential Φ pl (horizontal red line).…”
Section: Clps Versus Eepmentioning
confidence: 99%
“…In a realistic experiment the procedure to verify that the emission current is sufficient for shifting V fl,em as close as possible to Φ pl is to measure V fl,em as function of the EEP heating power P heat . It is very helpful that for increasing heating power the transition from the cold floating potential V fl towards Φ pl (being more positive than V fl by a few time T e -equation (1)) is usually rather abrupt and that above a certain value of P heat the value of V fl,em almost saturates (see for instance [10,30,35,36]). Also figure 1 illustrates the rather abrupt transition of the floating potential of an unheated, or only slightly heated EEP from that of a CLP (horizontal blue line) to that of an EEP, being close to the plasma potential Φ pl (horizontal red line).…”
Section: Clps Versus Eepmentioning
confidence: 99%
“…The probe itself can be made of a variety of materials, including platinum, tungsten, graphite and LaB 6 , but the greatest benefit of heating with a laser is that there is no potential distribution across the probe. Because of this, laser-heated probes have attracted attention from the fusion community in recent years [51][52][53][54][55]. Particularly noteworthy is the movable laser-heated emissive probe designed by Schrittwieser et al as shown in figure 17 [52].…”
Section: Laser Heatingmentioning
confidence: 99%
“…Most common are current-heated wire loops [10,11] but also laser heated probes have recently gained momentum [12,13]. The emitted electron current reduces the difference between the floating and the plasma potential to (4):…”
Section: Emissive Surfacementioning
confidence: 99%